Analisis Kekuatan dan Ketahanan Kejut Material Safety Helmet sesuai Standar SNI ISO 3873:2012 - Kusminah, Imah Luluk; Natsir A, Haidar; Wardani, Dianita; Dayanti, Tri (Politeknik Caltex Riau, 2023)
Work accident is an undesirable and unexpected event that can cause human and/or property casualties (Permenaker No. 03/MEN/1998). In Indonesia, the number of work accidents in the construction sector is still relatively high. Based on BPJS Employment data, in 2019 there were 77,295 cases of work accidents in the construction sector. Based on this, Occupational Safety and Health in carrying out construction work is given great attention. One of the most important and always required PPE is a safety helmet. Based on the many needs for PPE helmets, many brands of safety helmets are sold on the market without knowing their advantages and materials, many accidents have occurred, and many helmets have broken and other failures. Based on this, research was carried out on the analysis of compressive strength and durability of SNI and non-SNI safety helmet materials. The aim of this research is to determine whether the compressive strength and shock resistance of safety helmet materials comply with standards. The research used a qualitative method by testing safety helmets. The test results showed that the SNI safety helmet passed the pressure and shock resistance tests, while the non-SNI safety helmet did not pass the pressure test but still met the shock resistance test. This value will be used as a reference for innovating safety helmet materials.